DC 마그네트론 스퍼터링법을 이용한 광촉매박막(TiO₂, TiO-N)제조 및 오염물질 제거에 관한 연구 - 정원상(Weon Sang Jeong); 박상원(Sang Weon Park) (Daehan hwan'gyeong gonghag hoeji, 2005)
[ $TiO_2$ ] was deposited by DC magnetron sputtering on glass surface under various sputtering parameters such as discharge power($0.6{\sim}5.2\;kW$, substrate temperature($R.T{\sim}350^{°}C$), Ar and $O_2$ flow ratio with $0{\sim}50\;sccm$($Ar+O_2$ 90 sccm) and about 1 mtorr of pressure. TiO-N thin film was prepared under same sputtering conditions for $TiO_2$ thin film except flow ratio($Ar+O_2+N_2$ 90 sccm). The sheet resistance of thin films deposited under these parameters was measured to analyze electronic characteristic and thin film's thickness(${α}$-step), surface roughness(AFM) and formation construction(FE-SEM, XRD) were also measured to draw optimal sputtering parameters. In order to evaluate photo-activity of thin film($TiO_2$, TiO-N) made in optimal parameters for removal of pollutants, toluene among VOCs and Suncion Yellow among reactive dyes were chosen to probe organic compounds for photo-degradation. It was shown that the photo-catalytic thin films had a significant photo-activation for the chosen contaminants and especially TiO-N thin film showed maximum efficiency of 33% for toluene(5 ppm) removal in visible-light range. [ $TiO_2$ ]박막은 DC 마그네트론 스퍼터링법을 이용하여 다양한 스퍼터링 파라미터(전력 $0.6{\sim}5.2\;kw$, 기판온도 실온${\sim}350^{°}C$, 산소량 $0{\sim}50\;sccm$($O_2+Ar$ 90 sccm, 압력은 약 1 mtorr))를 통하여 증착되었다. TiO-N박막도 가스의 유량비를 제외하고는 $TiO_2$박막과 같은 스퍼터링 조건하에서 증착되었다. 이러한 스퍼터링 파라미터에서 증착된 박막의 전기적 특성을 분석하기 위하여 시트저항을 측정하였고, 박막의 두께(${α}$-step), 표면 거칠기(AFM), 형성 조직(FE-SEM, XRD)을 분석하여 최적 스퍼터링 파라미터를 도출하였다. 최적 스퍼터링 파라미터에서 제조된($TiO_2$, TiO-N)박막을 이용하여 광활성도를 평가하기 위하여 VOCs물질 중 toluene, 반응성 염료인 Suncion Yellow를 대상 물질로 선정하여 적용성 연구를 수행하였다. 실험에서 광촉매 박막은 적용물질에 대해서 광활성을 양호하게 보였으며, 특히 TiO-N광촉매 박막은 가시광 영역에서도 최대 33%의 톨루엔(5 ppm) 제거 효율을 나타내었다.